Utilizing allogeneic venous grafts to solve the problem of vascular defects and reconstruction in pancreatic surgery: a retrospective cohort study - Lin Zhou; Shao-cheng Lyu; Han-xuan Wang; Hua Fan; Tao Jiang; Ren Lang; Qiang He (Frontiers in Medicine, 2026)
Background Extensive vascular invasion or defects after resection significantly limit the feasibility of radical pancreatic surgery, underscoring the value of effective vascular reconstruction techniques. This study evaluates a novel approach to vascular reconstruction using allogeneic venous grafts (AVGs) in pancreaticoduodenectomy and pancreatectomy. Methods This retrospective cohort study included 187 patients with biliary or pancreatic malignancies or lesions presenting with various types of venous invasion who underwent pancreatic resection with vascular reconstruction using AVGs. The R0 resection rate, long-term patency rate of reconstructed vessels, and overall survival (OS) outcomes were evaluated. Univariate and multivariate Cox regression and logistic regression analyses were performed to identify independent risk factors for postoperative vascular stenosis and poor survival. Results All patients presented with variable extents of vascular defects and anatomical sites of vascular invasion, including the portal vein–superior mesenteric vein confluence ( n = 110), superior mesenteric vein ( n = 50), portal vein ( n = 25), inferior vena cava ( n = 1), and left renal vein ( n = 1). The postoperative complication rate was 33.2%, and the perioperative mortality rate was 7.0% both of which were comparable across different AVG reconstruction configurations. Excluding benign lesions, the overall R0 resection rate was 92.2% (166/180) across the malignant cohort, specifically 92.3% (132/143) in patients with pancreatic cancer, and 90.0% (27/30) in those with cholangiocarcinoma. The median follow-up duration was 88.0 months. Cumulative graft stenosis rates at 1-year, 2-year, and 3-year postoperatively were 18.4, 21.8, and 33.3%, respectively. Median overall survival and disease-free survival were 13 and 9 months, respectively, with 5-year overall survival and disease-free survival rates of 12.2 and 12.7%. The type of AVG used for vascular reconstruction had no significant short-term or long-term oncological outcomes (both p > 0.05). Conclusion The use of AVGs is a feasible and effective technique for vascular reconstruction following major venous resection in patients with locally advanced pancreatic and biliary malignancies. Its application achieved favorable R0 resection rates and acceptable long-term patency and survival outcomes.